Audiovisual Learning Media Based on Local Wisdom Values of the Baduy Tribe Community to Grow Student Character - Yulianto, Fazri; Winarno; Mintasih Indriayu (International Journal of Elementary Education, 2023)
Character building can be done by integrating local wisdom values. The values of the local wisdom of the Baduy people can be integrated into learning to shape student character. The integration process can be done by developing learning media. The purpose of this study was to develop audio-visual learning media based on local wisdom values of the Baduy community on social studies theme 7 sub-theme 2 in class IV to grow student character. This type of research is R&D research with the ADDIE model. The subjects of the research trial were 4th-grade elementary school students. Methods of data collection conducted through product validation and distribution of questionnaires. The data collection instrument was carried out, namely through the distribution of validation questionnaires and student character questionnaires. The steps in analysing the product developed are expert validation analysis consisting of material experts and media experts as well as student responses. Based on the results of the assessment, it can be concluded that audiovisual learning media based on the local wisdom values of the Baduy people have validity, feasibility, and effectiveness for use in developing student character. Good learning media can help students learn local wisdom in society.